2019
DOI: 10.1186/s12920-019-0490-y
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanisms driving physiological changes after long duration space flights revealed by quantitative analysis of human blood proteins

Abstract: BackgroundThe conditions of space flight have a significant effect on the physiological processes in the human body, yet the molecular mechanisms driving physiological changes remain unknown.MethodsBlood samples of 18 Russian cosmonauts who had conducted long-duration missions to the International Space Station were collected 30 days before launch and on the first and seventh days after landing.ResultsA panel of 125 proteins in the blood plasma was quantitated by a well-established and highly regarded targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…20 Functionally, these cardiovascular changes are associated with significant cardiovascular deconditioning as reflected by reduced maximal oxygen uptake in astronauts returning to Earth after long-duration spaceflight. 21 Further evidence for direct vascular injury during spaceflight was suggested by Kashirina et al, 22 who found that the myeloid-related protein-14 (S100A9), a member of the S100 family of proteins that regulates myeloid cell function and inflammation, was reliably elevated after exposure to space flight. S100A9 plays an important role in augmenting vascular inflammation, where genetic knockouts have identified a specific role in recruiting leukocytes to sites of vascular injury.…”
Section: Vascular Damage and Inflammation During Space Travelmentioning
confidence: 98%
See 2 more Smart Citations
“…20 Functionally, these cardiovascular changes are associated with significant cardiovascular deconditioning as reflected by reduced maximal oxygen uptake in astronauts returning to Earth after long-duration spaceflight. 21 Further evidence for direct vascular injury during spaceflight was suggested by Kashirina et al, 22 who found that the myeloid-related protein-14 (S100A9), a member of the S100 family of proteins that regulates myeloid cell function and inflammation, was reliably elevated after exposure to space flight. S100A9 plays an important role in augmenting vascular inflammation, where genetic knockouts have identified a specific role in recruiting leukocytes to sites of vascular injury.…”
Section: Vascular Damage and Inflammation During Space Travelmentioning
confidence: 98%
“…Kashirina et al 22 used targeted mass spectrometry to study the effects long-duration missions to the ISS on 125 blood proteins from 18 cosmonauts. Proteins involved in coagulation (factor XI, fibrinogen, fibrinopeptide A, and the serpin plasminogen activator inhibitor-3) and acute phase reactions (haptoglobin) were increased on the first day after spaceflight.…”
Section: Hypercoagulation During Space Travelmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a few instances were CPT tubes shattered in the centrifuge and plasma could not be salvaged. Plasma can be used to validate or refute previous studies, including cytokine panel 10,26 , exosomal RNA-seq 25,32 , extracellular vesicle microRNA 30 , and proteomic 20,[27][28][29] results. PBMCs were also collected, aliquoted into 6 cryovials per CPT, and stored in liquid nitrogen after slowly cooled in a Mr. Frosty to -80°C.…”
Section: Blood Collection and Derivativesmentioning
confidence: 99%
“…The goal is to assess the impact of these changes on health and consequently, on the safety and survival of the crew members. It is well-known that microgravity leads to a myriad of body alterations including bone and muscle mass loss, cardiovascular deconditioning, impaired exercise capacity, immune-deficiency, and alterations of peripheral metabolism (6)(7)(8). To prevent the development of these physiological modifications during spaceflights, international space agencies have put a lot of effort into the development of countermeasures.…”
mentioning
confidence: 99%